Strategic Reconfiguration in the Generative Era - Lina Marlina (Manexia: Journal of Business, Management, and Creative Economy, 2025)
Contemporary organizational environments are marked by shifting patterns of strategic judgment, capability development, and symbolic value creation. Rather than reflecting linear technological progress, recent transformations highlight how mediated decision processes reshape managerial cognition, engagement dynamics, and brand meaning. Emerging perspectives in dynamic capabilities, behavioral strategy, and branding scholarship suggest that competitive advantage increasingly depends on governance, orchestration, and interpretive diversity. This work advances a conceptual view of strategy as an evolving architecture in which agency, authenticity, and organizational learning are continuously reconfigured under conditions of structural change.